Implementasi Penerimaan Peserta Didik Baru dengan Sistem Zonasi di Kabupaten Kudus untuk Pemenuhan Hak Konstitusional Warga Negara dalam Bidang Pendidikan - Elinda Nur Hidayah; Achmad Achmad (Res Publica: Jurnal Hukum Kebijakan Publik, 2021)
ABSTRACT:This legal research aims to know the application of the PPDB Zone System in the fulfillment of constitutional rights in the field of education in Kabupaten Kudus, and the obstacles faced. Legal research is empirical or non-doctrinal research. The types of data used are primary data in the form of observations and interviews, as well as secondary data of law. Data collection techniques are carried out by collecting library studies of legal materials related to research as well as data obtained from field observations and interviews. Education is the duty and authority of the Regional Government, so the Government of Kabupaten Kudus is obliged to organize education based on the zonation system by establishing its organization for the fulfillment of the Constitutional Rights in the field of education. In the establishment of the Decision of the Ministry of Education and Culture Number 421/10163 About Acceptance of New Students in Senior High School (SMA) and Vocational High School (SMK) in the State Province of Java Middle Teaching Year 2019/2020 and the decision of the Head of the Department of Education, Youth, and Sports of Kabupaten Kudus on implementation of the zoning system in freeing students who come from outside the area that has the closest distance with the state school of Kabupaten Kudus can enter the area of school zoning in Kabupaten Kudus. The regulation has basically met the fulfillment of constitutional rights in the field of education, but in its implementation there are still obstacles such as the administrative territory of Kabupaten Kudus that entered the zoning and only reached 2-3 villages around the school due to the uneven spread of schools and centralized in the city. This shows that there are some aspects that are slightly contrary to the constitutional right in the field of education.Keywords: zone system; Kabupaten Kudus; PPDB; constitutional rights.